2020
DOI: 10.1007/s10964-020-01228-8
|View full text |Cite|
|
Sign up to set email alerts
|

The Role of Perceived Inter-Ethnic Classroom Climate in Adolescents’ Engagement in Ethnic Victimization: For Whom Does it Work?

Abstract: Immigrant and minority youth are at risk of experiencing victimization due to their ethnic, cultural, or religious background. Despite an increasing number of studies that aims at understanding the consequences of being the target of such negative experiences, little attention has been paid to the factors that might counteract the occurrence of ethnic victimization. The present study aimed to address this gap in knowledge by investigating the possible role of school context. Specifically, the present study exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 36 publications
3
23
0
1
Order By: Relevance
“…Another noteworthy finding of the study is that, while being male is a common denominator of all three non-normative groups, having an immigrant background is only a risk factor for engagement in non-ethnicity-based victimization, and engagement in both forms of victimization. The observed gender difference is consistent with previous research showing that boys are more at risk of engagement in both general (e.g., Sentse et al 2015 ) and ethnic victimization (e.g., Bayram Özdemir and Özdemir 2020 ). One possible explanation for the gender difference is related to the differences in emotional and cognitive skills between males and females.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Another noteworthy finding of the study is that, while being male is a common denominator of all three non-normative groups, having an immigrant background is only a risk factor for engagement in non-ethnicity-based victimization, and engagement in both forms of victimization. The observed gender difference is consistent with previous research showing that boys are more at risk of engagement in both general (e.g., Sentse et al 2015 ) and ethnic victimization (e.g., Bayram Özdemir and Özdemir 2020 ). One possible explanation for the gender difference is related to the differences in emotional and cognitive skills between males and females.…”
Section: Discussionsupporting
confidence: 90%
“…The findings also indicate that there are relatively more adolescents involved in non-ethnically based victimization than in ethnicity-based victimization, which might be related to the motives of different types of peer victimizers. Specifically, ethnicity-based victimization has a clear motive, founded in prejudiced beliefs (Bayram Özdemir et al 2016 ; Caravita et al 2019 ) or low tolerance toward immigrants (Bayram Özdemir and Özdemir 2020 ). In the current data, only 5% of adolescents had low positive attitudes toward immigrants (i.e., the percentage of adolescents who scored 2 or below on the positive attitudes toward immigrant scale).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The social dynamics in classrooms have implications for students' psychosocial functioning (Wang 2009) and academic growth (Reyes et al 2012). Recent studies have also shown that common norms and values in a classroom setting may have an impact on students' inter-group attitudes (Gniewosz and Noack 2008;Isac et al 2012;Schachner et al in press) and relationships (Bayram Özdemir and Özdemir 2020;Bayram Özdemir et al 2018;Schachner et al 2015). For example, a study focusing on adolescents in Germany investigated the influence of different indicators of the classroom climate on adolescents' intolerance in their attitudes toward foreigners.…”
Section: The Role Of Perceived Classroom Social Climatementioning
confidence: 99%